The Factors Influence to Competitive Performance of Small Firms Using the Internet in Northeastern Thailand - Wonginchan, Surasak; Promphakping, Baupun (International Review of Management and Marketing, 2017)
This article is quantitative research which aims to explore the factors influencing competitive performance of small firms using the Internet in Northeastern Thailand. The interview was conducted with 285 small firms that use the Internet. They were selected by stratified random sampling, which have fewer than 10 employees and have run the business for more than 1 year. Descriptive statistics are employed for data analysis in order to explain the characteristics of the sample group by frequency, percentage, average, standard deviation, and maximum and minimum values. Besides, interpretation of competitive performance of small firms is done with the 5-level criteria, from the least to the most. Also, inferential statistics are used to test the hypothesis about the factors affecting competitive performance of small firms with the Internet according to the study. Standardized Coefficient of Regression: Î² is used with the level of significance at 0.05 and R-Square value from regression line in order to tell about variation of competitive performance of small firms with the Internet (Dependent Variable) influenced by independent variables, including 1) structure of small firms, 2) use of the Internet, and 3) external surroundings of small firms. Keywords: Small Firms, Competitive performance, Using the Internet, Northeastern Thailand JEL Classification: L25